(untitled) (Journal of Civil Engineering Researchers, 2024)
In recent years, the use of activated alkaline slag concretes (AASC), has had a wide perspective in civil engineering science due to its many environmental benefits (due to the reduction of the emission of CO2 gas in the air) and high resistance to impact loads. is in this article, a mixed design of ordinary portland cement concrete (OPCC) containing 500 kg/m3 of portland cement as a control concrete and a mixed design of AASC containing granulated blast furnace slag (GBFS) was made, and the impact resistance of the concrete was tested under the weight-drop impact test (WDIT). It was evaluated at temperatures of 21, 300 and 600 ℃ at the age of 90 days. The obtained results indicate that the increase in temperature has caused a drop in the results of the WDIT, so that in OPCC, the energy absorbed and the flexibility index of concrete samples at a temperature of 600 ℃ drop by 76.92% and it obtained 86.95% improvement compared to 21 ℃ temperature, while in active alkali concrete, these figures brought 66.66 and 14.28% drop in results, respectively. In this regard, the number of impacts required for the occurrence of initial cracks and failure in the concrete sample had a downward trend with increasing temperature. In this experimental research, AASC showed superior results compared to OPCC. The results obtained from the analysis of the images of the scanning electron microscope (SEM) on the concrete samples overlapped with the other tests of this research.